Imaging of resuscitation and emergency resuscitation devices—Lessons learned from post mortem computed tomography. (June 2019) - Bolster, Ferdia; Ali, Zabiullah; Fowler, David; Daly, Barry
Highlights: Describes complications associated with cardiopulmonary resuscitation identifiable with PMCT. Review of commonly used resuscitation assist devices and associated complications. Abstract: This pictorial essay describes the use and value of post mortem computed tomography (PMCT) in imaging potential complications related to cardiopulmonary resuscitation and those related to commonly used pre-hospital medical resuscitation devices.